Impedimetric study of the electrocatalytic oxidation of alcohols by nickel-Schiff base metallopolymer: Potential application for forensic identification of alcoholic beverage contaminants by multivariate data analysis - Olean-Oliveira, André [UNESP]; Trevizan, Heitor F. [UNESP]; Cardoso, Celso X. [UNESP]; Teixeira, Marcos F.S. [UNESP] (Elsevier, 2023)
The present paper presents a systematic electrochemical impedance study on the electrooxidation of methanol, ethanol, 1-propanol, ethylene glycol and glycerol by a sensor based on nickel-salen metallopolymer. As a second step, the application simulated the device in the identification of contamination in alcoholic beverages by principal component analysis (PCA). By studying electrochemical impedance, we verified that the reactivity of alcohols on the device is directly related to pKa values and polarity index. By multivariate analysis, it was possible to set up a system that differentiates the types of alcohol with impedimetric variables. The identification distance between the groups allowed the differentiation of mixed samples from the groups containing ethanol-methanol and ethanol-ethylene glycol.
Keywords: Alcohol oxidation; Alcohol polarity index; Electrocatalysis; Impedimetric measurements; Principal component analysis